DISAIN DAN PABRIKASI MESIN PLANTING BENIH JAGUNG DENGAN SISTEM CULTIVATOR - Enzo W. B Siahaan (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
The design and manufacture of corn seeding planting machines with this cultivator system is one of the simplest and more productive technological innovations to help the community of entrepreneurs and farmers in completing the work of planting corn seeds in large areas. Maize cultivation can still be developed and become an excellent effort in Dairi Regency to see the area and the land available and supported by the fertile climate and soil as well as the people who like to plant maize. This is also offset by an increase in corn prices of maize commodities. To improve the corn production process, it requires a machine / tool that can plant corn seeds efficiently, a more productive way of working, and greater production capacity. The corn seed planting machine consists of several standard components such as: 1) 4-step gasoline motor, 1: 50 reducer speed, pegs, pulleys, belts / belts, chains, gears and bearings, 2) key components done by machining process that is: cradle frame, driving shaft, blade / blade, screw arm, screw cultivator. The machines / equipment used in the construction process, and the main components are: machine, machine, machine, hand grinding machine, deep thread tap, and welding transformer. From the design and fabrication process to the process start from the process of making the main component and assembling process that is done, hence produce one unit of planting plant of corn seed with cultivator system according to the desired design with result of production capacity test 258 seed / minute.